PENGARUH STIMULASI PEMBERIAN TABLET HISAP VITAMIN CTERHADAP PENINGKATAN SEKRESI SALIVA PADA PASIEN GAGALGINJAL KRONIK YANGMENJALANI TERAPI HEMODIALISADI RS PKU MUHAMMADIYAH GOMBONG - Utoyo, Bambang; Yuwono, Podo; Tri Kusumawati, Wening (LPPM STIKES MUHAMMADIYAH GOMBONG, 2016)
Chronic renal failure is a progressive deterioration in kidney function and irreversible, in where the body is unable to maintain fluid balance and electrolyte metabolism. Inpractice, patients must limit fluid diet to prevent complications. However, such action may affect some aspect of the human body, that is dry mouth or xerostomiadue to decrease saliva production. To reduce patient complaint, actions which can be done is to stimulate gland salivary with chemical stimulation using lozenges sour taste vitamin C. The aim of this study is to the determine the stimulation effect of the vitamin C lozenges provision to increase salivary secretion in patients with chronic renal failure undergoing hemodialysis therapy in PKU Muhammadiyah Gombong Hospital.This study used a quasi experimental design with pretest — postest design. Samples amounts 42 respondents, consisting of 21 respondents control and 21 respondents intervention by using Purposive Sampling technique. Data analysis technique using Paired t Test to determine whether there were significant differences in salivary secretion in the pretest and postest.Based on a statistical test Paired t Test found a significant increase in the salivary secretion between pretest saliva and postest one intervention group with a value of p=0,003. In conclusion, stimulation of vitamin C lozenges giving has affect to increase saliva secretion in patients with chronic renal failure undergoing hemodialysis therapy in PKU Muhammadiyah Gombong Hospital. Keywords: stimulation, secretion of saliva, chronic renal failure